Commentary: The Road to Success in Nursing Education - Sandra M. LeFort (Nursing Leadership, 2004)
[This paper is a commentary on Shared Decision-Making in Nursing Education by Francine M. Parker and Arlene H. Morris.] The paper by Parker and Morris presents two main ideas. First, shared decision-making (SDM) is identified as the desired governance model within schools or faculties of nursing thus making the point that educational decisions should be collaborative in nature involving all those affected by the decisions. The ideas of teamwork, putting group goals first, respecting differences and building trust are critical elements in successful implementation of SDM. Second, the paper highlights a model of decision-making (ABCS model by Nye and Capelluti, 2003) that differentiates between levels of involvement in decision-making: autocratic, bureaucratic, consensus and student involvement. In other words, the authors argue that while the umbrella governance approach for schools and faculties of nursing should be one of SDM, the "art" of governance using SDM involves negotiating agreement about what kinds of concerns or issues need full participation and which do not.